Mesozooplankton biodiversity, vertical assemblages, and diel migration in the western tropical Pacific Ocean revealed by eDNA metabarcoding and morphological methods - Feng, Yunzhi; Sun, Dong; Shao, Qianwen; Fang, Chen; Wang, Chunsheng (Frontiers in Marine Science, 2022)
Zooplankton plays a crucial role in marine ecosystems. However, due to issues with morphological identification and sampling methods, knowledge of their biodiversity and community structure in the vast pelagic zone of the western tropical Pacific Ocean is still limited compared with other areas in the North Pacific Ocean. In this study, we used environmental DNA (eDNA) metabarcoding and morphological identification approaches to investigate mesozooplankton's biodiversity and vertical assemblages in the western tropical Pacific Ocean from the surface to 1000 m deep. Two different barcodes were used in metabarcoding: mitochondrial cytochrome oxidase I (COI) and small subunit ribosomal RNA genes (18S). Our results showed that eDNA metabarcoding revealed 2-4 times more medusae taxa than morphological processing. Both methods detected that small copepod species were dominant in the community and six of the top-10 most abundant copepod genera overlapped. Morphological results showed that mesozooplankton communities were classified into three groups: epipelagic (0–200 m), upper mesopelagic (200-500 m), and lower mesopelagic (500–1000 m). And eDNA results showed distinct vertical variations of mesozooplankton communities within the epipelagic. Both methods showed that the dominant genera Clausocalanus, Paracalanus, and Calocalanus exhibited diel patterns in relative abundance, demonstrating that the eDNA method can capture diel vertical migration (DVM) signals of copepods. Overall, our results indicate that eDNA metabarcoding is an effective and efficient tool for the study and monitoring of mesozooplankton diversity and vertical assemblages in the open sea.